Flexibilization and possible labor reform in Argentina: a study about digital representations of Clarin and La Nacion - Coscia, Vanesa; Perbellini, Melina (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2020)
The purpose of the paper is to analyze narratives circulating in the mass media, particularity the main media newspapers: Clarín y La Nación in their digital versions. The study focuses on the relationship of neoliberalism – labor reform – media representations; and we propose a critical analysis of these mass media discourses privileged readings (Hall, 1981) about a possible Labor Reform in Argentina, since 2017. The aim of this study is to identify discursive mechanisms and representation strategies used by these media to produce and reproduce certain points of view about flexibilization and labor reforms. The questions are: What is visualized, what is emphasized and what is hidden in these media digital narratives when informing about a possible Labor Reform? In which way are ideological bases established to create a social consensus on this issue? What are the social meanings that the media from assign to work, labor flexibilization, precarization? How the employer sector and trade unions are represented by mass media? Methodologically, a socio-semiotic approach is used, that focuses on the analysis of the social meanings about labor flexibilization, reforms and precariousness, from the formal elements, content and sources, included in the digital news on this theme. We consider that the privileged representations and social meanings that the media —particularly the more concentrated media with a hierarchical space in the national media structure— assign to labor reform, conflicts, labor flexibilization, work conditions, are an interesting variable to explore the cultural construction of common sense and social stereotypes in neoliberal contexts.